2012
DOI: 10.1096/fj.12-210419
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the symbiont Cardinium in Culicoides (Diptera: Ceratopogonidae) vector species is associated with land surface temperature

Abstract: Prevalence of infection by bacterial symbionts may reflect their interactions with the host and has been shown to be correlated with environmental factors. Yet, it is still unclear whether infection by symbionts is determined by environmental factors affecting the early or imago stage of the host. Here, we identified and localized the symbiont Candidatus Cardinium hertigii (Bacteroidetes) in sympatric Culicoides biting midge species, examined its abundance, and studied its association with environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 56 publications
(75 reference statements)
3
56
1
3
Order By: Relevance
“…Recent studies have identified Wolbachia and Cardinium in Culicoides species collected in Japan, Israel, and the United Kingdom. These studies used conventional PCR assays to reveal a relatively low prevalence of both Wolbachia (1/34) and Cardinium (8/34) (13)(14)(15). In the present study, 20 species of Culicoides, collected predominately in southeastern Australia, were screened for the presence of these endosymbionts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have identified Wolbachia and Cardinium in Culicoides species collected in Japan, Israel, and the United Kingdom. These studies used conventional PCR assays to reveal a relatively low prevalence of both Wolbachia (1/34) and Cardinium (8/34) (13)(14)(15). In the present study, 20 species of Culicoides, collected predominately in southeastern Australia, were screened for the presence of these endosymbionts.…”
Section: Discussionmentioning
confidence: 94%
“…Screening studies conducted using conventional PCR assays detected Wolbachia DNA in a single Culicoides paraflavescens individual in Japan (13). "Candidatus Cardinium hertigii" (Bacteroidetes), another bacterial endosymbiont which also has a range of influences on its host insect, has been detected in four Culicoides species in Japan, two in Israel, and two in the United Kingdom (13)(14)(15). Endosymbiotic diversity in Australian Culicoides species has not been investigated previously, nor has a comparative analysis of Cardinium divergence in different Culicoides species from diverse geographical locations been reported.…”
mentioning
confidence: 99%
“…Dead midges were removed and kept in absolute ethanol at 4°C until their identity and infection status were assessed individually as described above. Individual midges were subjected to DNA extraction and specific "Candidatus Cardinium" PCR detection as described by Morag et al (7). Under optimal conditions and under starvation, experiments were repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Accuracy in temperature measurements is important for applying integrated pest management (IPM) in both forest and agricultural settings (e.g., Fand et al, 2014;Faye et al, 2014), for exploring the possible effects of global warming on ecosystems and organisms (e.g., Logan et al, 2004;Gutierrez et al, 2009;Ponti et al, 2009) and for developing strategies for the management of vector-borne diseases of humans and animals over large geographic areas (e.g., Rogers et al, 1996;Gilioli and Mariani, 2011;Amek et al, 2012;Chen and Hsieh, 2012). Recently, land surface temperature (LST) data derived from satellites have been proposed as a possible source of temperature data to be fed into insect population models and used to explore ecological and environmental questions (Carbajal de la Fuente et al, 2009;Coops et al, 2009;Chuang et al, 2012;Lensky and Dayan, 2011;Morag et al, 2012;Steinman et al, 2012;Blum et al, 2013;Aharonson-Raz et al, 2014). Lensky and Dayan (2011) used LST data to investigate the variability in the developmental rate of an agricultural pest (Heliothis sp.)…”
Section: Introductionmentioning
confidence: 99%